Development of prednisolone-containing eye drop formulations by cyclodextrin complexation and antimicrobial, mucoadhesive biopolymer - Bíró T; Horvát G; Budai-Szűcs M; Csányi E; Urbán E; Facskó A; Szabó-Révész P; Csóka I; Aigner Z (Dove Medical Press, 2018)
Tivadar Bíró,1 Gabriella Horvát,1 Mária Budai-Szűcs,1 Erzsébet Csányi,1 Edit Urbán,2 Andrea Facskó,3 Piroska Szabó-Révész,1 Ildikó Csóka,1 Zoltán Aigner1 1Institute of Pharmaceutical Technology and Regulatory Affairs, University of Szeged, Szeged, Hungary; 2Department of Clinical Microbiology, Faculty of Medicine, University of Szeged, Szeged, Hungary; 3Ophthalmology Department, Faculty of Medicine, University of Szeged, Szeged, Hungary Purpose: The formulation of topical ophthalmic products with appropriate therapeutic effect and patient compliance is a major challenge. To increase the efficiency of the ocular delivery of the drug, the enhancement of water solubility and the contact time of the drug on the surface of the cornea are necessary. In this work, prednisolone (PR)-containing eye drops were formulated with antimicrobial, mucoadhesive biopolymer and PR–cyclodextrin inclusion complex. This approach can be used for the development of innovative ophthalmic formulations. Materials and methods: After adjusting the optimal physiological parameters, the amount of the required cyclodextrin for the highest penetration of PR was determined by dialysis membrane diffusion study. The viscosity, surface tension and mucoadhesion of the eye drops were measured. The microbiological effectiveness of zinc-hyaluronate (ZnHA) was investigated by a standard method of the European Pharmacopoeia. Results: In this case, no significant difference of surface tension was measured in products with different amounts of cyclodextrin. According to the results of the tensile test, ZnHA as a mucoadhesive biopolymer improves the mucoadhesion of ophthalmic products. The antimicrobial stability of formulations preserved by ZnHA meets requirement B of the European Pharmacopoeia. Conclusion: It can be stated that the innovative PR-containing compositions are suitable for producing mucoadhesive, properly preserved aqueous ophthalmic solutions with increased bioavailability attributes. Keywords: pharmaceutical formulation, zinc-hyaluronate, ocular drug delivery, microbiological stability, membrane diffusion